1988
DOI: 10.4319/lo.1988.33.3.0364
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal variation of dimethyl sulfide and dimethylsulfoniopropionate concentrations in nearshore waters1

Abstract: Concentrations of biogenic dimethyl sulfide (DMS) in seawater around mainland Britain in winter and summer (1985) ranged from 1 to 1,100 ng S (DMS) liter-'. The mean winter DMS concentration was 4 ng S (DMS) liter-' compared with the mean summer concentration of 220. Analyses of phytoplankton species composition in summer indicate that the main sources of DMS were coccolithophores, various dinoflagellates including the bloom species Gyrodinium aureolum, and certain unidentified taxa of small flagellates. Conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
251
2
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(282 citation statements)
references
References 15 publications
28
251
2
1
Order By: Relevance
“…During SOFeX the response of DMS inside the patch was very similar to what was found previously for IronExII (48), although that experiment was conducted in the warm equatorial environment and observations lasted only 8 days. DMS is an important sulfurcontaining trace gas (49) produced by phytoplankton (50,51) and during the grazing of phytoplankton by microzooplankton (52). Emission of DMS from ocean waters is a major source of cloud condensation nuclei in the unpolluted marine environment.…”
Section: Resultsmentioning
confidence: 99%
“…During SOFeX the response of DMS inside the patch was very similar to what was found previously for IronExII (48), although that experiment was conducted in the warm equatorial environment and observations lasted only 8 days. DMS is an important sulfurcontaining trace gas (49) produced by phytoplankton (50,51) and during the grazing of phytoplankton by microzooplankton (52). Emission of DMS from ocean waters is a major source of cloud condensation nuclei in the unpolluted marine environment.…”
Section: Resultsmentioning
confidence: 99%
“…Seasonal variations DMSP and DMS have been previously studied in the Southern North Sea (SNS) based on field measurements and model applications (Turner et al, 1988;Kwint and Kramer, 1996;van den Berg et al, 1996;Stefels et al, 1995;van Duyl et al, 1998;Archer et al, 2002;. All of these studies reported a marked seasonal cycle in DMS(P) with a maximum in spring (April-May) corresponding to the Phaeocystis bloom followed by a decrease to low winter values.…”
Section: Introductionmentioning
confidence: 99%
“…Dimethylsulfoniopropionate (DMSP) is the precursor compound to DMS [10] and DMSP is synthesised by phytoplankton, and the amount of DMSP is highly dependent on the species of plankton present. [11] Although direct emission of DMS from plankton in the laboratory has been observed, [12] it has not been observed in the oceans and more typically it is the action of grazers and viruses on the plankton community that results in significant levels of DMSP in the water column; [13,14] typically, the highest levels of DMSP and DMS are associated with the senescence of a plankton bloom.…”
Section: The Devil Is In the Detailmentioning
confidence: 99%